Identifikasi Drug Related Problems (DRPs) pada Pasien Penyakit Jantung Koroner di Instalasi Rawat Inap CVBC RSUP Prof. Dr. R. D. Kandou Manado - Laloan, Carmelita; Wiyono, Weny I.; Mpila, Deby A. (e-CliniC, 2025)
Abstract: Patients with coronary heart disease (CHD) are prone to Drug Related Problems (DRPs) due to the many therapies received by patients. This study aimed to identify the prevalence of DRPs in each category of CHD patients. This was a descriptive and retrospective study using medical records of CHD patients during the period September-November 2023 who fulfilled the inclusion criteria. The results obtained 64 CHD patients as samples. There were 27 patients (42.19%) who had the potential to experience DRPs with 31 cases of DRPs in the identified DRPs categories including indications without therapy (77.41%) and therapy without indications (22.59%). There were no DRPs in the categories of ineffective drugs, dose too high, and dose too low. In conclusion, the therapy obtained by coronary heart disease patients in the CVBC inpatient installation of Prof. Dr. R. D. Kandou Hospital Manado still experienced DRPs, especially in the categories of indication without therapy and therapy without indication. Keywords: coronary heart disease; drug related problems    Abstrak: Pasien dengan penyakit jantung koroner (PJK) rentan mengalami Drug Related Problems (DRPs) karena terapi yang diterima pasien cukup banyak. Penelitian ini bertujuan untuk mengidentifikasi prevalensi kejadian DRPs pada setiap kategori dari pasien PJK. Jenis penelitian ialah deskriptif retrospektif dengan pengambilan data rekam medik pasien PJK yang memenuhi kriteria inklusi selama periode September-November 2023. Hasil penelitian mendapatkan 64 pasien PJK sebagai sampel. Terdapat 27 pasien (42,19%) yang berpotensi mengalami DRPs dengan 31 kejadian DRPs pada kategori DRPs indikasi tanpa terapi (77,41%) dan terapi tanpa indikasi (22,59%); tidak terdapat kejadian DRPs pada kategori obat tidak efektif, dosis terlalu tinggi, dan dosis terlalu rendah. Simpulan penelitian ini ialah terapi yang diperoleh pasien penyakit jantung koroner di instalasi rawat inap CVBC RSUP Prof. Dr. R. D. Kandou Manado masih mengalami kejadian Drug Related Problems, terutama pada kategori indikasi tanpa terapi dan terapi tanpa indikasi. Kata kunci: penyakit jantung koroner; drug related problems